2019
DOI: 10.1126/science.aar2038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for hormonal control of heart regenerative capacity during endothermy acquisition

Abstract: Tissue regenerative potential displays striking divergence across phylogeny and ontogeny, but the underlying mechanisms remain enigmatic. Loss of mammalian cardiac regenerative potential correlates with cardiomyocyte cell-cycle arrest and polyploidization, as well as the development of postnatal endothermy. We reveal that diploid cardiomyocyte abundance across 41 species conforms to Kleiber’s law−the ¾-power law scaling of metabolism with bodyweight−and inversely correlates with standard metabolic rate, body t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
353
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 291 publications
(372 citation statements)
references
References 55 publications
14
353
2
3
Order By: Relevance
“…These include maturation of cardiac fibroblasts, activity of macrophages and other immune cells, ECM composition and rigidity, as well as physiological hypoxia and hormonal regulation. 14,28,41,42 Investigating the discordance in timing of cardiac maturation and regenerative capacity in pigs could be useful to define relative contributions of multiple cell types and physiological factors in heart regeneration. Here, we show that ECM remodeling is significant by P7 in pigs, contributing to increased rigidity of the matrix, while maturational collagen remodeling continues to 6mo.…”
Section: What Dictates Postnatal Regenerative Capacity Of the Mammalimentioning
confidence: 99%
“…These include maturation of cardiac fibroblasts, activity of macrophages and other immune cells, ECM composition and rigidity, as well as physiological hypoxia and hormonal regulation. 14,28,41,42 Investigating the discordance in timing of cardiac maturation and regenerative capacity in pigs could be useful to define relative contributions of multiple cell types and physiological factors in heart regeneration. Here, we show that ECM remodeling is significant by P7 in pigs, contributing to increased rigidity of the matrix, while maturational collagen remodeling continues to 6mo.…”
Section: What Dictates Postnatal Regenerative Capacity Of the Mammalimentioning
confidence: 99%
“…3B-D). The heart weight to body weight ratio did not significantly differ between Myh6-Cre;Vdr f/f knockout mice We recently showed that TH signaling regulates CM proliferative potential, but mice with deficiency in TH receptor activation in CMs have ~30% mononuclear CMs at P14, implicating the existence of other pathways that contribute to CM binucleation in the neonatal period 11 . We next investigated whether loss of GR or VDR signaling affect CM proliferative potential in combination with loss of TH signaling.…”
Section: Resultsmentioning
confidence: 91%
“…dosed with propylthiouracil (PTU) -a potent inhibitor of TH synthesis -from birth through postnatal day 14 (P14) show significantly increased mononuclear CM percentage and CM proliferation 11 . These mononuclear CMs and CM proliferation phenotypes are also observed in mutant mice in which TH signaling is specifically inactivated in CMs 11 . These mutant mouse hearts also display enhanced recovery after MI as indicated by cardiac contractile functions and fibrosis one month post-surgery.…”
mentioning
confidence: 99%
“…To test if thyroid hormone signaling is necessary for Coq10a expression in the heart, we analyzed its transcript levels in mice that express a dominant negative form of thyroid hormone receptor alpha (Thra DN ) to suppress thyroid hormone signaling specifically in cardiomyocytes (Myh6-Cre;Thra DN ), recently generated by our laboratory (19). RNA-seq analyses of Myh6-Cre;Thra DN hearts at P14 demonstrated that the gene expression of Coq10a was reduced to one-third compared to control hearts ( Figure 2B).…”
Section: Thyroid Hormone Signaling Activates Coq10a Gene Expressionmentioning
confidence: 99%
“…Mice procedures were conducted in accordance with the Institutional Animal Care and Use Committee (IACUC) of the University of California, San Francisco. CD-1 (Charles River) and against Thra-GFP were described in our previous paper (19).…”
Section: Animalsmentioning
confidence: 99%